Advances in Iranian linguistics - Larson, Richard K.; Moradi, Sedigheh; Samiian, Vida (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2020)
"This volume brings together selected papers from the first North American Conference in Iranian Linguistics, which was organized by the linguistics department at Stony Brook University. Papers were selected to illustrate the range of frameworks, diverse areas of research and how the boundaries of linguistic analysis of Iranian languages have expanded over the years. The contributions collected in this volume address advancing research and complex methodological explorations in a broad range of topics in Persian syntax, morphology, phonology, semantics, typology and classification, as well as historical linguistics. Some of the papers also investigate less-studied and endangered Iranian languages such as Tat, Gilaki and Mazandarani, Sorani and Kurmanji Kurdish, and Zazaki. The volume will be of value to scholars in theoretical frameworks as well as those with typological and diachronic perspectives, and in particular to those working in Iranian linguistics"--
Advances in Iranian linguistics: an introduction / Sedigheh Moradi -- Syntactic and semantic constraints on pronoun and anaphor resolution in Persian / Elias Abdollahnejad and Dennis Ryan Storoshenko -- A multi-dimensional approach to classification of Iran's languages / Erik Anonby, Amos Hayes and Robert Oikle -- The additive particle in Persian: a case of morphological homophony between syntax and pragmatics / Jila Ghomeshi -- The pronoun-to-agreement cycle in Iranian: subjects do, objects don't / Geoffrey Haig -- The suffix that makes Persian nouns unique / Masoud Jasbi -- The meaning of the Persian object marker rā: what it is not, and what it (probably) is / Masoud Jasbi -- Topic agreement, experiencer constructions, and the weight of clitics / Thomas Jügel and Pollet Samvelian -- Another look at Persian rā: a single formal analysis of a multi-functional morpheme / Simin Karimi and Ryan Walter Smith -- The Ezafe construction revisited / Richard Larson and Vida Samiian -- Quantitative meter in Persian folk songs and pop lyrics / Mohsen Mahdavi Mazdeh -- Stripping structures with negation in Persian / Vahideh Rasekhi -- Oblique marking and adpositional constructions in Tat: a mosaic of dialectal convergence and divergence / Murad Suleymanov
Includes bibliographical references and indexes
Description based on online resource; title from digital title page (viewed on July 29, 2020).
eBooks on EBSCOhost
Keywords: Iranian languages -- Congresses; Iranian languages -- Grammar -- Congresses; Linguistics -- Iran -- Congresses; Iran -- Languages -- Congresses; Langues iraniennes -- Congrès.; Langues iraniennes -- Grammaire -- Congrès.; Linguistique -- Iran -- Congrès.; Iran -- Langues -- Congrès.; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Iranian languages; Iranian languages -- Grammar; Language and languages; Linguistics; Iran; Conference papers and proceedings